Role of DNA polymerase η in the bypass of abasic sites in yeast cells - Zhao, Bo (Oxford University Press, 2004)
Abasic (AP) sites are major DNA lesions and are highly mutagenic. AP site-induced mutagenesis largely depends on translesion synthesis. We have examined the role of DNA polymerase η (Polη) in translesion synthesis of AP sites by replicating a plasmid containing a site-specific AP site in yeast cells. In wild-type cells, AP site bypass resulted in preferred C insertion (62%) over A insertion (21%), as well as −1 deletion (3%), and complex event (14%) containing multiple mutations. In cells lacking Polη (rad30), Rev1, Polζ (rev3), and both Polη and Polζ, translesion synthesis was reduced to 30%, 30%, 15% and 3% of the wild-type level, respectively. C insertion opposite the AP site was reduced in rad30 mutant cells and was abolished in cells lacking Rev1 or Polζ, but significant A insertion was still detected in these mutant cells. While purified yeast Polα effectively inserted an A opposite the AP site in vitro, purified yeast Polδ was much less effective in A insertion opposite the lesion due to its 3′→5′ proofreading exonuclease activity. Purified yeast Polη performed extension synthesis from the primer 3′ A opposite the lesion. These results show that Polη is involved in translesion synthesis of AP sites in yeast cells, and suggest that an important role of Polη is to catalyze extension following A insertion opposite the lesion. Consistent with these conclusions, rad30 mutant cells were sensitive to methyl methanesulfonate (MMS), and rev1 rad30 or rev3 rad30 double mutant cells were synergistically more sensitive to MMS than the respective single mutant strains.